Diseño social aplicado a la innovación de productos artesanales locales de la ciudad de Riobamba - Garzón Tenezaca, Nicol Estefanía (2022)
Currently, there is a devaluation of handicrafts, which have long been a legacy passed down from generation to generation and constitute an essential source of income for the economy of the people who work as artisans. The objective of this study was to innovate local handicraft products from the social design approach, through which new paths of meaning are generated, creating constructions of meaning and humanism in the material and symbolic production of the contemporary world. It is a qualitative approach to transversal cut. Therefore, the use of tools based on observation prevailed. Two handicrafts were selected: those developed by the ceramic artisan Eduardo Ortega and the cattail artisan Guadalupe Ramón. The instruments used were observation cards, pictorial boards (ethnographic guidelines), technical cards, and a life book. The techniques used were interpretation of observation cards, interpretation of vision boards, and construction of the life book. As a result of the research, two key elements were proposed: first, a basic brand manual that demonstrates the process of personal branding based on the "Visual Branding Canvas" model. The second key element offered is the methodological application of the creative direction manual for the created brand, based on the "CAMPER" model. To conclude, it was possible to detect the potential for innovation that the handicrafts currently have, to have a personal brand that identifies and positions them in the market, and to integrate the methodology of the creative direction manual to improve marketing strategies through digital communication channels.